Silicon-carbon negative electrode material for battery and preparation method of silicon-carbon negative electrode material
By depositing nanosilicon particles on the porous graphene matrix and forming a carbon cladding layer, the problem of excessive expansion rate of silicon carbon materials under fast charging and discharge conditions is solved, and better cycling performance and lower expansion rate are achieved, extending the cycle life of lithium-ion batteries and enhancing safety.
Patent Information
- Application Number
- CN202411664156.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-25
AI Technical Summary
Under high current density or fast charging and discharging conditions, the expansion rate caused by lithium ion embedding and deintercalation of silicon carbon materials is too high, affecting the cycle life and safety of the battery.
A porous graphene matrix is used as a substrate for nanosilicon particles, and a carbon cladding layer is formed on its surface by vapor deposition to form a silicon carbon negative electrode material with a more delicate and uniform pore structure and a more stable framework structure.
It significantly reduces the expansion rate of silicon-carbon negative electrode material, improves its circulation performance and rate performance, extends the cycle life of lithium-ion secondary batteries, and enhances the safety of the battery.
Smart Images

Figure BDA0005144191550000091 
Figure BDA0005144191550000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of batteries, and in particular relates to a silicon-carbon negative electrode material for batteries and a preparation method thereof, an electrode, and a battery. Background Art
[0002] First, silicon-carbon materials have good thermal stability. Due to their unique crystal structure, silicon-carbon materials can maintain stable performance in high-temperature environments without significant structural changes or performance degradation. This makes silicon-carbon materials have broad application prospects in high-temperature environments, such as high-temperature furnaces, aerospace and other fields. Secondly, silicon-carbon materials also have good corrosion resistance. Whether in acidic, alkaline or neutral environments, silicon-carbon materials can show excellent corrosion resistance and will not change their performance due to environmental changes. This characteristic makes silicon-carbon materials have wide application potential in chemical, metallurgical and other industries. In addition, silicon-carbon materials also have good conductivity and insulation. This makes silicon-carbon materials widely used in electronics, electricity and other fields. Especially in the field of batteries, silicon-carbon materials are regarded as a new type of battery negative electrode material with great potential due to their high specific energy and high charge and discharge efficiency. With the rapid development of products such as electric vehicles and wearable devices, the application prospects of silicon-carbon materials in the field of batteries are becoming more and more broad. In terms of environmental protection and sustainable development, silicon-carbon materials also show great potential. Because silicon-carbon materials have good recyclability and reusability, they can effectively reduce resource consumption and environmental pollution. At the same time, silicon-carbon materials can also be combined with other materials to form new composite materials with higher performance and wider applications.
[0003] In summary, silicon-carbon materials have become a new type of material that has attracted much attention due to their unique chemical composition, physical properties and broad application prospects. With the continuous advancement of science and technology and the continuous development of the industry, silicon-carbon materials will demonstrate their unique value and potential in more fields. Silicon has a theoretical specific capacity of 4200mAh / g, and can store more lithium ions than graphite negative electrodes. The battery energy density is relatively high, which effectively improves the battery life and mileage. Because of its high theoretical capacity, low lithium insertion and extraction potential, environmental friendliness, and abundant reserves, it is regarded as the most promising next-generation lithium battery negative electrode material.
[0004] However, the pore structure of silicon-carbon materials is easy for lithium ions to be embedded and de-embedded, especially under high current density or fast charge and discharge conditions. Under these conditions, lithium ions may be embedded and de-embedded more quickly, resulting in more dramatic stress changes inside the electrode material and changes in volume, which in turn causes a higher expansion rate. First, an excessively high expansion rate will lead to poor contact between it and the material, increase resistance, and affect the charge and discharge efficiency of the battery. At the same time, as the charge and discharge cycle proceeds, the expansion and contraction of the silicon-carbon negative electrode material will lead to the generation of cyclic stretching stress. Long-term cycles will cause structural fatigue and loosening of the silicon-carbon negative electrode material, thereby reducing the cycle life of the battery. Secondly, expansion will increase the stress inside the battery, which may cause damage to the battery or even short circuit, thus causing safety hazards. In addition, expansion may also cause changes in the internal structure of the battery, affect the thermal stability of the battery, and increase the risk of thermal runaway of the battery. The expansion of the negative electrode will also lead to stress concentration inside the battery cell, increase the internal pressure of the battery cell, and may cause rupture and leakage of the battery cell shell. In addition, expansion will also cause the movement path of lithium ions inside the battery cell to become longer, increase resistance, and affect the charge and discharge efficiency of the battery cell. Summary of the invention
[0005] In order to solve the above-mentioned problems of high expansion rate and poor cycle performance, the present invention provides a silicon-carbon negative electrode material for a battery and a preparation method thereof.
[0006] The silicon-carbon negative electrode material for a battery described in the present invention comprises a porous graphene matrix, nano-silicon particles and a carbon coating layer; the nano-silicon particles are dispersedly distributed inside and / or on the surface of the porous graphene matrix; the carbon coating layer completely or partially covers the surface of the porous graphene matrix and / or the nano-silicon particles.
[0007] Compared with the skeleton structure and pore structure of porous biochar, porous graphene has both a flake structure and a pore structure, and has a more delicate and uniform pore structure and a more stable and strong skeleton structure. Therefore, when porous graphene is used as a substrate for nano-silicon deposition, the silicon-carbon negative electrode material has better cycle performance and lower expansion rate. In addition, porous graphene has high conductivity due to its unique three-dimensional continuous structure, high crystallinity and no macro cracks. Therefore, the high ion diffusion rate and high electron conduction rate of porous graphene will make the silicon-carbon negative electrode material have better rate performance.
[0008] The specific surface area of the silicon-carbon negative electrode material is 100 m 2 / g or less. Within this specific surface area range, the side reactions occurring on the surface of silicon-carbon negative electrode material particles are relatively few and the stability is relatively high. The specific surface area of silicon-carbon negative electrode material is preferably 80m 2 / g or less, more preferably 50m 2 / g or less, more preferably 30m 2 / g or less.
[0009] The silicon content of the silicon-carbon negative electrode material is 30%-70%. Within this silicon content range, the silicon-carbon negative electrode material of the present invention has a very high reversible capacity. The silicon content of the silicon-carbon negative electrode material is preferably 40%-60%, more preferably 45%-55%.
[0010] The size of the silicon grains fitted by the X-ray diffraction pattern of the above silicon-carbon negative electrode material is less than 8nm. Within this silicon grain size range, when the silicon-carbon negative electrode material particles undergo a cycle of lithium ion insertion and extraction, the particles expand less and are not easy to break, so that the cycle expansion of the lithium ion secondary battery using the material is small and the cycle is stable. The size of the silicon grains fitted by the XRD of the silicon-carbon negative electrode material is preferably less than 4nm, and more preferably less than 2nm.
[0011] The particle size D50 of the silicon-carbon negative electrode material is 2μm-20μm. Within the range of the particle size D50, the silicon-carbon negative electrode material particles can better receive electrons and ions, increase the rate of electrochemical reactions, and thus increase the capacity of the lithium-ion secondary battery using the material. In addition, within the range of the particle size D50, the irreversible capacity loss is also small, so it may show more stable performance during long-term cycles. The particle size D50 of the silicon-carbon negative electrode material is preferably 3μm-15μm, more preferably 5μm-13μm.
[0012] The tap density of the silicon-carbon negative electrode material is 0.1-2.0 g / cm 3 Within this tap density range, the internal pores can accommodate volume expansion and reduce SEI damage, while avoiding the decrease in particle mechanical strength and the loss of volume specific energy. The tap density of silicon-carbon negative electrode materials is preferably 0.3-1.5 g / cm 3 , more preferably 0.5-1.1 g / cm 3 .
[0013] The present invention also provides a method for preparing the silicon-carbon negative electrode material for a battery, comprising the following steps:
[0014] (1) dispersing nano-silicon particles inside and / or on the surface of a porous graphene matrix by a vapor deposition method;
[0015] (2) Covering the surface of the porous graphene matrix and / or nano-silicon particles with a carbon layer completely or partially by vapor deposition.
[0016] The present invention also provides an electrode, which comprises the above-mentioned silicon-carbon negative electrode material for a battery or the silicon-carbon negative electrode material prepared using the above-mentioned method for preparing the silicon-carbon negative electrode material for a battery.
[0017] The present invention also provides a battery, which comprises the above-mentioned electrode.
[0018] Beneficial effects: The silicon-carbon negative electrode material for batteries of the present invention has a smaller expansion rate and a better ion diffusion rate and electron conduction rate when in use. The battery prepared using this silicon-carbon negative electrode material has a smaller cycle expansion, better cycle stability and rate performance. DETAILED DESCRIPTION
[0019] The present invention will now be further described in detail by way of examples, but the present invention is not limited to the examples.
[0020] The present invention is a silicon-carbon negative electrode material for a battery, comprising a porous graphene matrix, nano-silicon particles and a carbon coating layer; the nano-silicon particles are dispersedly distributed inside and / or on the surface of the porous graphene matrix; the carbon coating layer completely or partially covers the surface of the porous graphene matrix and / or the nano-silicon particles.
[0021] The method for preparing the silicon-carbon negative electrode material for a battery of the present invention comprises the following steps.
[0022] (1) Nano-silicon particles are dispersedly distributed inside and / or on the surface of the porous graphene matrix. In actual experiments, nano-silicon particles are naturally dispersed in at least one of the following three situations: "inside", "on the surface", or "inside and on the surface" of the porous graphene matrix.
[0023] Place the porous graphene substrate in a reaction furnace, and continuously introduce an inert protective gas into the reaction furnace; adjust the speed of the reaction furnace and start the furnace chamber heating system; when the insulation point is reached, start to introduce a certain flow of silicon-containing precursor into the deposition furnace until the insulation is completed. The obtained nano-silicon particles are dispersedly distributed inside and / or on the surface of the porous graphene matrix. The above-mentioned reaction furnace can be one or more of a CVD furnace and a fluidized bed. The above-mentioned inert protective gas is one or more of nitrogen, argon, hydrogen, helium, neon or krypton. The rotation speed of the above-mentioned reaction furnace is 1 to 40 Hz, preferably 5 to 35 Hz, and more preferably 10 to 30 Hz. The inlet flow rate of the above-mentioned silicon-containing precursor is 0.5-10L / min, preferably 1-7L / min, and more preferably 1.5-5L / min; the above-mentioned silicon-containing precursor is a silicon-containing gas including one or more silane gases selected from monosilane, disilane, trisilane, dichlorosilane, trichlorosilane, and tetrachlorosilane; the insulation temperature is 400°C to 1000°C, preferably 450°C to 900°C, and more preferably 500°C to 800°C; the insulation time is 100-1000min, preferably 200-800min, and more preferably 300-600min.
[0024] (2) The carbon coating layer completely or partially covers the surface of the porous graphene matrix and / or nano-silicon particles.
[0025] On the basis of step (1), continue to heat up to the second insulation point, and continue to introduce a certain flow of carbon-containing precursor until the insulation ends. After cooling to room temperature, discharge the material to obtain silicon-carbon negative electrode material. The above-mentioned continued heating rate is 2-10°C / min, the insulation temperature is 400°C-1000°C, preferably 450°C-900°C, and more preferably 550°C-850°C; the insulation time is 30-600min, preferably 60-480min, and more preferably 120-360min; the above-mentioned carbon-containing precursor is one or more of methane, ethane, propane, butane, acetylene and propylene.
[0026] Example 1-1
[0027] The specific surface area of the porous graphene substrate used is 1100 m 2 / g, particle size D50 is 10μm, tap density is 0.39g / cm 3 , take 1.5kg of the above porous graphene matrix and place it in a fluidized bed, continue to introduce argon gas to maintain the fluidized state and inert atmosphere. Turn on the heating, adjust the speed to 10Hz, introduce 3L / min of monosilane at 520℃, and stop introducing monosilane after 180min. Raise the temperature to 580℃, start introducing acetylene for carbon coating, turn off the heating after completion, and cool to room temperature to obtain a silicon-carbon negative electrode material.
[0028] Performance Testing
[0029] For the obtained silicon-carbon negative electrode material, the silicon content was determined by using Elte ELEMENTRAC CS-i high-frequency infrared carbon-sulfur analyzer; the specific surface area of the negative electrode active material was tested by using Quantachrome Instruments NOVA4200e specific surface area tester; the particle size distribution was determined by using Dandong BetterSize 2600 laser particle size analyzer; the tap density was determined by using Dandong Better BT-301 tap density tester; and the silicon crystal size was determined by using Rigaku MiniFlex600 X-ray diffractometer.
[0030] Take 95 parts of the above silicon-carbon negative electrode material, 2.5 parts of conductive additives, and 2.5 parts of binders, slurry, coat, dry, and roll in an aqueous system to obtain a silicon-containing negative electrode plate. The above silicon-containing negative electrode plate, diaphragm, lithium sheet, and stainless steel gasket are stacked in sequence and sealed after adding 200 μL of electrolyte to form a 2016-type lithium-ion half-cell. The capacity and discharge efficiency are measured using a small (micro) current range device of Wuhan Blue Electric Electronics Co., Ltd.
[0031] Take 30 parts of the above silicon-carbon negative electrode material, 64 parts of artificial graphite, 2.5 parts of conductive additives, and 3.5 parts of binder, and apply them in an aqueous system, then dry and roll them to obtain negative electrode sheets. The negative electrode sheets are cut, vacuum-baked, wound together with the paired lithium cobalt oxide positive electrode sheets and diaphragms, and loaded into aluminum-plastic shells of corresponding sizes. A certain amount of electrolyte is injected and degassed and sealed. After formation, a lithium-ion full battery of about 3.2Ah is obtained. The capacity and efficiency of the full battery at different rates are measured using the BTS-5V6A battery tester of Shenzhen Xinwell Electronics Co., Ltd., and the long-cycle stability is measured at 1C / 1C.
[0032] The silicon content of the silicon-carbon negative electrode material of this embodiment is measured to be 31.03%, and the specific surface area is 91m 2 / g, and the silicon grain size is 0.7nm.
[0033] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 1348.1 mAh / g, and the first-cycle coulombic efficiency (FCE) is 85.7%.
[0034] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 80.4%, the cell expansion rate of the full battery after 1000 cycles is 10.2%, and the retention rate after 1000 cycles is 79.3%. The results are shown in Table 1.
[0035] Example 1-2
[0036] The process of Example 1-2 is similar to that of Example 1-1, except that the time for introducing monosilane is changed to 200 min.
[0037] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this embodiment was measured to be 33.33%, and the specific surface area was 84m 2 / g, and the silicon grain size is 1.1nm.
[0038] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 1416.0 mAh / g, and the first-cycle coulombic efficiency (FCE) is 87.3%.
[0039] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 85.7%, the cell expansion rate of the full battery after 1000 cycles is 10.5%, and the retention rate after 1000 cycles is 80.2%. The results are shown in Table 1.
[0040] Examples 1-3
[0041] The process of Example 1-3 is similar to that of Example 1-1, except that the time for introducing monosilane is changed to 230 min.
[0042] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this embodiment was measured to be 36.51%, and the specific surface area was 71m 2 / g, and the silicon grain size is 1.2nm.
[0043] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 1509.7 mAh / g, and the first-cycle coulombic efficiency (FCE) is 89.9%.
[0044] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 88.2%, the cell expansion rate of the full battery after 1000 cycles is 10.9%, and the retention rate after 1000 cycles is 80.8%. The results are shown in Table 1.
[0045] Examples 1-4
[0046] The process of Example 1-4 is similar to that of Example 1-1, except that the time for introducing monosilane is changed to 250 min.
[0047] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this embodiment was measured to be 38.46%, and the specific surface area was 64m 2 / g, and the silicon grain size is 1.4nm.
[0048] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 1567.4 mAh / g, and the first-cycle coulombic efficiency (FCE) is 91.3%.
[0049] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 90.3%, the cell expansion rate of the full battery after 1000 cycles is 11.4%, and the retention rate after 1000 cycles is 81.4%. The results are shown in Table 1.
[0050] Examples 1-5
[0051] The process of Example 1-5 is similar to that of Example 1-1, except that the time for introducing monosilane is changed to 280 min.
[0052] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this embodiment was measured to be 41.18%, and the specific surface area was 48m 2 / g, and the silicon grain size is 1.5nm.
[0053] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 1647.5 mAh / g, and the first-cycle coulombic efficiency (FCE) is 91.8%.
[0054] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 92.3%, the cell expansion rate of the full battery after 1000 cycles is 11.7%, and the retention rate after 1000 cycles is 82.7%. The results are shown in Table 1.
[0055] Examples 1-6
[0056] The process of Example 1-6 is similar to that of Example 1-1, except that the time for introducing monosilane is changed to 350 min.
[0057] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this embodiment was measured to be 46.67%, and the specific surface area was 27m 2 / g, and the silicon grain size is 1.6nm.
[0058] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 1809.6 mAh / g, and the first-cycle coulombic efficiency (FCE) is 93.3%.
[0059] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 93.1%, the cell expansion rate of the full battery after 1000 cycles is 12.2%, and the retention rate after 1000 cycles is 83.9%. The results are shown in Table 1.
[0060] Examples 1-7
[0061] The process of Example 1-7 is similar to that of Example 1-1, except that the time for introducing monosilane is changed to 370 min.
[0062] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this embodiment was measured to be 48.05%, and the specific surface area was 25m 2 / g, and the silicon grain size is 1.6nm.
[0063] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 1850.5 mAh / g, and the first-cycle coulombic efficiency (FCE) is 93.5%.
[0064] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 93.2%, the cell expansion rate of the full battery after 1000 cycles is 12.4%, and the retention rate after 1000 cycles is 85.8%. The results are shown in Table 1.
[0065] Examples 1-8
[0066] The process of Example 1-8 is similar to that of Example 1-1, except that the time for introducing monosilane is changed to 400 min.
[0067] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this embodiment was measured to be 50.09%, and the specific surface area was 23m 2 / g, and the silicon grain size is 1.7nm.
[0068] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 1908.0 mAh / g, and the first-cycle coulombic efficiency (FCE) is 93.6%.
[0069] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 93.5%, the cell expansion rate of the full battery after 1000 cycles is 12.7%, and the retention rate after 1000 cycles is 85.9%. The results are shown in Table 1.
[0070] Examples 1-9
[0071] The process of Example 1-9 is similar to that of Example 1-1, except that the time for introducing monosilane is changed to 420 min.
[0072] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this embodiment was measured to be 51.22%, and the specific surface area was 22m 2 / g, and the silicon grain size is 1.7nm.
[0073] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 1944.0 mAh / g, and the first-cycle coulombic efficiency (FCE) is 93.9%.
[0074] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 93.9%, the cell expansion rate of the full battery after 1000 cycles is 13.3%, and the retention rate after 1000 cycles is 86.1%. The results are shown in Table 1.
[0075] Examples 1-10
[0076] The process of Example 1-10 is similar to that of Example 1-1, except that the time for introducing monosilane is changed to 450 min.
[0077] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this embodiment was measured to be 52.94%, and the specific surface area was 19m 2 / g, and the silicon grain size is 1.7nm.
[0078] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 1994.8 mAh / g, and the first-cycle coulombic efficiency (FCE) is 93.5%.
[0079] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 93.5%, the cell expansion rate of the full battery after 1000 cycles is 13.8%, and the retention rate after 1000 cycles is 85.6%. The results are shown in Table 1.
[0080] Embodiment 1-11
[0081] The process of Example 1-11 is similar to that of Example 1-1, except that the time for introducing monosilane is changed to 480 min.
[0082] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this embodiment was measured to be 54.55%, and the specific surface area was 14m 2 / g, and the silicon grain size is 1.8nm.
[0083] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 2042.2 mAh / g, and the first-cycle coulombic efficiency (FCE) is 92.8%.
[0084] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 93.1%, the cell expansion rate of the full battery after 1000 cycles is 14.5%, and the retention rate after 1000 cycles is 82.5%. The results are shown in Table 1.
[0085] Examples 1-12
[0086] The process of Example 1-12 is similar to that of Example 1-8, except that the insulation temperature for introducing monosilane is changed to 580°C.
[0087] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this embodiment was measured to be 50.02%, and the specific surface area was 24m 2 / g, and the silicon grain size is 3.8nm.
[0088] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 1908.0 mAh / g, and the first-cycle coulombic efficiency (FCE) is 92.1%.
[0089] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 90.3%, the cell expansion rate of the full battery after 1000 cycles is 18.9%, and the retention rate after 1000 cycles is 78.3%. The results are shown in Table 1.
[0090] Examples 1-13
[0091] The process of Example 1-13 is similar to that of Example 1-1, except that the time for introducing monosilane is changed to 580 min.
[0092] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this embodiment was measured to be 59.18%, and the specific surface area was 9m 2 / g, and the silicon grain size is 1.9nm.
[0093] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 2179.1 mAh / g, and the first-cycle coulombic efficiency (FCE) is 92.3%.
[0094] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 92.8%, the cell expansion rate of the full battery after 1000 cycles is 19.1%, and the retention rate after 1000 cycles is 77.7%. The results are shown in Table 1.
[0095] Examples 1-14
[0096] The process of Example 1-14 is similar to that of Example 1-1, except that the time for introducing monosilane is changed to 720 min.
[0097] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this embodiment was measured to be 64.29%, and the specific surface area was 8m 2 / g, and the silicon grain size is 3.9nm.
[0098] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 2329.7 mAh / g, and the first-cycle coulombic efficiency (FCE) is 91.9%.
[0099] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 92.4%, the cell expansion rate of the full battery after 1000 cycles is 24.3%, and the retention rate after 1000 cycles is 72.4%. The results are shown in Table 1.
[0100] Examples 1-15
[0101] The process of Example 1-14 is similar to that of Example 1-1, except that the time for introducing monosilane is changed to 900 min.
[0102] The same performance test was carried out, and the silicon content in the silicon-carbon negative electrode material of this embodiment was measured to be 69.23%, and the specific surface area was 8m 2 / g, and the silicon grain size is 7.3nm.
[0103] In this embodiment, the evaluation results of the half-cell containing the silicon-carbon negative electrode material are as follows: the first-cycle lithium delithiation capacity of the full cell is 2475.7 mAh / g, and the first-cycle coulombic efficiency (FCE) is 90.3%.
[0104] In this embodiment, the evaluation results of the full battery containing the silicon-carbon negative electrode material are: CD% (3C / 0.1C) is 84.0%, the cell expansion rate of the full battery after 1000 cycles is 30.9%, and the retention rate after 1000 cycles is 65.8%. The results are shown in Table 1.
[0105] Comparative Example 1
[0106] The processes of Comparative Example 1 and Examples 1-15 are similar, except that there is no carbon coating step.
[0107] The same performance test was carried out, and the silicon content in the negative electrode active material in this comparative example was measured to be 69.18%, and the specific surface area was 43m 2 / g, and the silicon grain size is 7.2nm.
[0108] In this comparative example, the evaluation results of the half-cell containing the negative electrode active material are as follows: the first-cycle lithium desorption capacity of the full cell is 1898.5 mAh / g, and the first-cycle coulombic efficiency (FCE) is 84.9%.
[0109] In this comparative example, the evaluation results of the full battery containing the negative electrode active material are: CD% (3C / 0.1C) is 72.5%, the cell expansion rate of the full battery after 1000 cycles is 35.5%, and the retention rate after 1000 cycles is 55.2%. The results are shown in Table 1.
[0110] Comparative Example 2
[0111] The process of Comparative Example 2 is similar to that of Examples 1-15, except that the substrate is replaced with porous biochar with the same physical property parameters.
[0112] The performance test was also carried out, and the silicon content in the negative electrode active material in this comparative example was measured to be 69.26%, and the specific surface area was 57m 2 / g, and the silicon grain size is 8.5nm.
[0113] In this comparative example, the evaluation results of the half-cell containing the negative electrode active material are as follows: the first-cycle lithium desorption capacity of the full cell is 1929.5 mAh / g, and the first-cycle coulombic efficiency (FCE) is 88.3%.
[0114] In this comparative example, the evaluation results of the full battery containing the negative electrode active material are: CD% (3C / 0.1C) is 80.1%, the cell expansion rate of the full battery after 1000 cycles is 32.3%, and the retention rate after 1000 cycles is 58.6%. The results are shown in Table 1.
[0115] Table 1 Performance parameters of silicon-carbon negative electrode materials in various embodiments and comparative examples
[0116]
[0117]
[0118] As can be seen from Table 1, because the porous graphene substrate has a more delicate and uniform pore structure and a more stable and strong skeleton structure, as well as a unique three-dimensional continuous structure, high crystallinity and no macro crack characteristics, compared with porous biomass carbon, the silicon-carbon negative electrode material with porous graphene as the substrate for nano-silicon deposition has better rate performance, better cycle performance and lower expansion rate. Especially in the silicon-carbon negative electrode material based on porous graphene. In addition, when the specific surface area, silicon content, and silicon grain size of the silicon-carbon negative electrode material are all in the most preferred range, the first-cycle lithium removal capacity, first-cycle coulomb efficiency, cycle expansion rate, and cycle retention rate of the lithium-ion secondary battery using the material are all in the optimal numerical range at the same time.
[0119] The above-mentioned technologies not specifically mentioned are all referred to the prior art.
[0120] Based on the above-mentioned ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above-mentioned description. The technical scope of the present invention is not limited to the contents of the specification.
Claims
1. A silicon-carbon negative electrode material for a battery, characterized in that: It comprises a porous graphene matrix, nano silicon particles and a carbon coating layer; the nano silicon particles are dispersedly distributed inside and / or on the surface of the porous graphene matrix; the carbon coating layer completely or partially covers the surface of the porous graphene matrix and / or the nano silicon particles.
2. The silicon-carbon negative electrode material for a battery according to claim 1, characterized in that: The specific surface area of the silicon-carbon negative electrode material is less than 100 m² / g, the silicon content is 30%-70%, and the size of the silicon grains fitted by XRD is less than 8 nm.
3. The silicon-carbon negative electrode material for a battery according to claim 2, characterized in that: The specific surface area of the silicon-carbon negative electrode material is less than 80 m² / g, the silicon content is 40%-60%, and the size of the silicon grains fitted by XRD is less than 4 nm.
4. The silicon-carbon negative electrode material for a battery according to claim 3, characterized in that: The specific surface area of the silicon-carbon negative electrode material is less than 50 m² / g, the silicon content is 45%-55%, and the size of the silicon grains fitted by XRD is less than 2 nm.
5. The silicon-carbon negative electrode material for a battery according to claim 4, characterized in that: The specific surface area of the silicon-carbon negative electrode material is less than 30 m² / g.
6. The method for preparing a silicon-carbon negative electrode material for a battery according to any one of claims 1 to 5, characterized in that: The steps include: (1) dispersing nano-silicon particles inside and / or on the surface of a porous graphene matrix by vapor deposition; (2) Covering the surface of the porous graphene matrix and / or nano-silicon particles with a carbon layer completely or partially by vapor deposition.
7. An electrode, characterized in that: A silicon-carbon negative electrode material for a battery comprising any one of claims 1 to 5 or a silicon-carbon negative electrode material prepared using the method for preparing a silicon-carbon negative electrode material for a battery according to claim 6.
8. A battery, characterized in that: Comprising the electrode according to claim 7.